Interaction of central obesity and sarcopenia on nutritional status in the community-dwelling older people. (March 2020) - Chang, Chin -Sung; Chang, Yin-Fan; Liu, Ping-Yen; Wu, Shin-Jiuan; Chiu, Ching-Ju; Chen, Chuan-Yu; Wu, Chih-Hsing
Highlights: 18 % of older people residents of a rural community were at risk for abnormal nutritional status. According to the Asian definition, the prevalence of central obesity and sarcopenia of the older people living in a rural community were 59.9 % and 10.4 %, respectively. Sarcopenic subjects without central obesity had highest proportion of abnormal nutritional status (65.4 %) as compared to the non-sarcopenic subjects with central obesity (12.8 %). The interaction effect between central obesity and sarcopenia on the nutritional status might reflect the dilemma of the obesity paradox when treating older people. Except the MNA, central obesity and sarcopenia might also be another surrogates for assessing the nutritional status of older people living in a rural community. Abstract: Objectives: To investigate the interrelationships between central obesity, sarcopenia and nutritional status in the elderly. Methods: We enrolled 501 elderly (women: 47.5 %) with complete datasets. Biochemical and anthropometric data were measured after an overnight fast. Basic characteristics, psychosocial and behavioral factors, nutritional status, and history of chronic disease came from structured questionnaires. Central obesity was defined as waist circumference ≥ 90 cm for men, ≥ 80 cm for women. Sarcopenia was defined by the Asian consensus. Nutritional status was assessed using Mini Nutritional Assessment scores: abnormal nutritional status ≤ 23.5. Multiple logistic regression analysis was done to determine the independent factors of an abnormal nutritional status. Results: Ninety (18.0 %) participants had an abnormal nutritional status, 300 (59.9 %) had central obesity, 52 (10.4 %) sarcopenia and 3 (0.6 %) sarcopenic obesity. Central obesity (OR = 0.455, 95 % CI: 0.244-0.847) and total lymphocyte count (OR = 0.526, 95 % CI: 0.315-0.880) were negatively and sarcopenia (OR = 3.170, 95 % CI: 1.485–6.767), current smoking (OR = 4.071, 95 % CI: 1.357–12.211), and total number of chronic diseases (OR = 1.484, 95 % CI: 1.234–1.785) were positively associated with abnormal nutritional status. An analysis of the combine effects of central obesity and sarcopenia on nutritional status showed that significantly fewer participants with central obesity but not sarcopenia had abnormal nutrition than participants with sarcopenia with or without central obesity (12.8 % vs 38.5 or 65.4 %, p < 0.001). Conclusions: Central obesity and sarcopenia were interactively associated with the nutritional status of older people living in a rural community.